EFFECT OF AZOSPIRILLUM BRASILENSE, AZOTOBACTER CHROOCOCCUM, ON THE GROWTH AND YIELD OF ORYZA SATIVA UNDER BIOFERTILIZERS - Pratibha Singh Chandel (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The application of biofertilizers has drawn interest recently as a sustainable substitute for chemical fertilisers in agriculture. Azotobacter and Azospirillum, two nitrogen-fixing bacteria, are essential for increasing soil fertility and fostering plant growth. The purpose of this study is to assess how inoculating rice cultivars with Azotobacter and Azospirillum as biofertilizers affects plant development, yield, nitrogen fixation, and soil health. According to the findings, inoculation with these advantageous bacteria considerably increases soil fertility and rice yield, offering a sustainable substitute for traditional fertilisers.